2012
DOI: 10.48550/arxiv.1206.4038
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A comparative study of long-baseline superbeams within LAGUNA for large $θ_{13}$

Abstract: The Daya Bay and RENO experiments have recently observed a non-zero θ 13 at more than 5σ CL. This has important consequences for future neutrino oscillation experiments. We analyze these within the LAGUNA design study which considers seven possible locations for a European neutrino observatory for proton decay, neutrino, and astroparticle physics. The megaton-scale detector would be an ideal target for a CERN-based neutrino beam with baselines ranging from 130 km to 2300 km. We perform a detailed study to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 85 publications
3
14
0
Order By: Relevance
“…So with only SM the short baseline like 130 Km seems to be better for good discovery reach of CP violation. This was observed earlier by different authors [13][14][15][16][17]. However, the short baseline may not be always better in presence of NSI which we discuss below.…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…So with only SM the short baseline like 130 Km seems to be better for good discovery reach of CP violation. This was observed earlier by different authors [13][14][15][16][17]. However, the short baseline may not be always better in presence of NSI which we discuss below.…”
Section: Resultssupporting
confidence: 64%
“…In figures 1, 2, 3 we have shown the NSI effect ∆ p in the particular oscillation channel ν µ → ν e (which is the most important channel for CP violation discovery) for different baseline length L and different neutrino energy E. It is found that oscillation probability P νµ→νe changes significantly in presence of NSI ε eµ and ε eτ in comparison to other NSIs for longer baselines and higher energies. It is known that in presence of SM interactions of neutrinos with matter the shorter baseline can give better discovery reach for CP violation [13][14][15][16][17]. However, as we have shown that in presence of NSI this may not be always true.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Phenomenological analyses for wide-band neutrino beams operating in the multi-GeV energy regime have shown that the sensitivity to neutrino oscillation parameters of a liquid-argon detector is similar to that of a Cherenkov detector of the mass ∼3-6 times larger, because of the lower efficiency of the latter for non-QE events [57,[80][81][82][83]. It has been argued that the reason lies in the imaging capabilities of the liquid-argon technology, able to identify protons in addition to lepton tracks [57], as opposed to Cherenkov detectors in which the information on CC events comes predominantly from the charged leptons.…”
Section: Oscillation Analysismentioning
confidence: 99%
“…In this work we assume the following detecting properties [23,24]. Whenever a neutrino interacts with the detector substance, the counting system reconstructs the energy and flavor of the incident neutrino and identifies the event with the corresponding energy bin.…”
Section: Numerical Analysismentioning
confidence: 99%